Nationalism and COVID in Belgium: A Surprisingly United Response in a Divided Federal Country. Issue 3 (3rd July 2021) - Sinardet, Dave; Pieters, Jade
Abstract: Belgium is considered as a very divided multinational and federal state, with conflicts between representatives of its two main language communities regularly threatening its sheer existence. Moreover, at the outbreak of the COVID 19-crisis, Belgium was in the middle of a political crisis: ten months of failed attempts to form a new federal government left a minority caretaker government to deal with the crisis. When the second wave arrived, a new federal government was formed but its composition was strongly different than the Flemish government, which was lead by the Flemish-nationalist N-VA, a situation of incongruence between governments that generally reinforces political conflicts within Belgium. All this means that a very fragmented, divisive and conflictual COVID-response could be expected. Therefore, it is surprising that the response was largely uniform and national response. There was a political consensus that measures should be the same over the entire territory. This article details the institutions, policies and communication that created this national response and also explains the reasons for it. It also focuses on the problems that the distribution of competences posed to execute the response and what it means for the nationalist movement as well as for possible future constitutional reform.